Magazines transition to digital : the case of Georgia - Osepashvili, Dali (2024)
The goal of this paper is to show the results of a study into how Georgian magazines adapted to a digital transition, the kind of innovations they used and the kind of challenges they faced. For this purpose, we use the qualitative approach - the semi-structured interview method. The study was conducted among editors and journalists (n=12) of the magazines from 1 March 2023 till 15 December 2023. In the digital age, magazines in Georgia have faced a number of challenges: it is not easy to retain readers for the print edition, and the tendency of readers to decline is gradually becoming more apparent.